The Influence of Profitability, Leverage, Firm Size, and Liquidity on Stock Prices: Evidence from the Pharmaceuticals and Healthcare Research Subsector Listed on the Indonesia Stock Exchange - Faturrahman, Ahmad Rai; Hakim, Astrid Dita Meirina (Jurnal Multidisiplin Sahombu, 2025)
This study investigates the relationship between profitability, leverage, firm size, and liquidity with stock price performance in the Indonesian pharmaceutical and healthcare research subsector. The research is motivated by the dynamic developments in capital markets where investors increasingly seek evidence of how fundamental indicators shape valuation. Using panel data regression, the analysis reveals that profitability, leverage, and liquidity do not exert a significant influence on stock prices, while firm size demonstrates a significant negative effect. This finding indicates that large companies in the subsector may face structural challenges and operational complexities that reduce investor confidence, despite the general expectation of scale advantages. The results emphasize that market participants consider qualitative aspects such as efficiency and adaptability more than sheer size. The study provides managerial implications for companies to strengthen efficiency and strategic focus, while offering guidance for investors in evaluating firm characteristics beyond conventional indicators